Rodzeństwo osoby niepełnosprawnej intelektualnie. Studium przypadku - Szarecka, Wioletta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Children with disabled siblings grow up in specific conditions. The case study presents the profile of a young woman living with a disabled brother. Because of her family situation she has become very understanding and tolerant of people with disabilities. She has no fear of the need to help them, is very responsible and has a sense of duty to such people. However, on the negative side, the woman is afraid of the genetic determinants of the disease and fears to start her own family. She is also afraid that her husband might have a negative attitude towards disability and she has ambivalent feelings about taking over the care of her brother.